The Influence of Magnesium on Blood Glucose Control (GAIMS Journal of Medical Sciences, 2025)
Background: Magnesium acts as a cofactor in glucose phosphorylation and numerous other enzymatic reactions. Its deficiency may contribute to insulin resistance, carbohydrate intolerance, and dyslipidemia. Reduced serum magnesium levels have been linked to the development of diabetic complications, including retinopathy, altered platelet function, cardiovascular disease, and hypertension. The present study aimed to examine the association between serum magnesium levels and glucose regulation.Materials and methods: Data from 256 patients who underwent serum testing for glucose, magnesium, glycated hemoglobin (HbA1c), insulin, and lipid profile between May 2024 and June 2025 were retrospectively analyzed. Based on glucose and HbA1c values defined by the 2017 American Diabetes Association guidelines, participants were categorized into three groups: non-diabetic, prediabetic, and diabetic. Intergroup comparisons were conducted using the Kruskal–Wallis H test and the Mann–Whitney U test.Results: Among the participants, 137 were nondiabetic, 85 were prediabetic, and 34 were diabetic, with median ages (range) of 40 years (24–55), 45 years (35–58), and 48 years (30–57), respectively. Magnesium levels differed significantly between the nondiabetic and diabetic groups, as well as between the prediabetic and diabetic groups (both p